Role of Food Allergy Education: Measuring Teacher Knowledge, Attitudes, and Beliefs. (June 2019) - Canon, Nicole; Gharfeh, Maya; Guffey, Danielle; Anvari, Sara; Davis, Carla M.
Introduction: Almost 6 million children suffer from food allergies with roughly 2 affected per classroom. Deficiencies in knowledge and discrepancies in attitudes within school staff when addressing food allergies are associated with barriers to care. In this study, school teacher knowledge, beliefs, and attitudes were measured before and after a food allergy educational session. Methods: Three hundred seventy-five personnel of similar age, socioeconomic status, ethnicity, and educational level completed the Chicago Food Allergy Research survey before and after a 1-hour educational session in 6 private schools in Houston randomly assigned into an intervention (n = 4) and control group (n = 2). Responses were measured using frequencies and percentages. The group score differences and survey question comparisons were evaluated with a linear mixed-effects model. Results: Posttest, the intervention group had knowledge scores 19.58% points higher than control (95% confidence interval = 16.62–22.53; P  < .001) with no differences pretest. Odds of agreeing that injectable epinephrine is important was higher in the intervention schools posteducation. Within the intervention group, personnel were more likely to agree to injectable epinephrine use for children posteducation. Conclusion: A 1-hour educational session improved knowledge and attitudes in personnel in the intervention schools. Given the growing prevalence of food allergy, the emphasis on food allergy education is crucial to allow for familiarization of the condition, early recognition of anaphylaxis, and promotion of injectable epinephrine use.